A Survey of Predaceous coccinellid beetles (Coleoptera: Coccinellidae) and their insect and mite preys in El-Beida city and its surrounding area, Libya - Amin, A.H.; El-Mabrouk, A.H. (Al-Mukhtar Journal of Sciences, 2002)
A study was conducted to survey predaceous coccinellid beetles and their insect and phytophagous mite preys in El-Beida city. Thirteen species of predaceous beetles were collected from orchard groves, vegetable crops, ornamental plants and wild plants. Some were observed as adults and larvae preying on aphids, scale insects, whiteflies mealy bugs and phytophagous mites. The results showed that Scymnus syriacus Mars. And Coccinella septempunctata L. were more abundant predators, and can be used as a biological control agents. The obtained data revealed that 3 species of predaceous coccinellid beetles, Cydonia isis Cr., Cydonia nilotica Muls. And Clitostethus arcuatus (Rossi) were newly recorded species in Libya.